2000
DOI: 10.1159/000014215
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Treatment of Endotoxic Shock with Monophosphoryl Lipid A in Newborn Rats

Abstract: Mortality due to gram-negative septic shock remains high despite advances in medical care. Induction of endotoxin tolerance might be a new treatment strategy to prevent septic shock in the newborn. The present study was performed to show that an injection in pregnant rats of monophosphoryl lipid A (MPL), a nontoxic derivative of lipopolysaccharide (LPS), induces tolerance to Salmonella enteritidis LPS and tumor necrosis factor alpha (TNF-α) in their offspring. MPL at a dose of 2 mg/kg was injected into pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Local AP concentrations reflect the host defense against endotoxin in the kidney [9], and during ischemia enzyme levels are markedly depleted, associated with the development of AKI [10]. Apart from local effects in the kidney, AP may attenuate the innate immune response, as dephosphorylation of endotoxin abolishes its biological activity and induces tolerance to subsequent endotoxin exposure [11]. In animal models of sepsis, AP administration attenuates the inflammatory response and reduces mortality [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Local AP concentrations reflect the host defense against endotoxin in the kidney [9], and during ischemia enzyme levels are markedly depleted, associated with the development of AKI [10]. Apart from local effects in the kidney, AP may attenuate the innate immune response, as dephosphorylation of endotoxin abolishes its biological activity and induces tolerance to subsequent endotoxin exposure [11]. In animal models of sepsis, AP administration attenuates the inflammatory response and reduces mortality [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical removal of one of these phosphate groups, resulting in the conversion of LPS to monophosphoryl lipid A (MPLA), abolished the toxicity of LPS (5). This MPLA has shown to have protective effects against experimental septic shock in animals (5,6) and to induce tolerance to endotoxin in humans (7).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have examined the effects of LPS treatment on the host response to live bacterial infections. Recent studies from our laboratory, and others, have demonstrated that mice primed with LPS have improved resistance to bacterial infections (23,39,40). However, the clinical applicability of LPS as a therapeutic or prophylactic agent is precluded by toxicity and a narrow therapeutic index in humans.…”
mentioning
confidence: 99%
“…The attenuated toxicity of MPLA is associated with reduced induction of proinflammatory cytokines such as tumor necrosis factor alpha (TNF-␣), interleukin-1␤ (IL-1␤), and gamma interferon (IFN-␥) during initial exposure (13,29). MPLA retains significant immunomodulatory activity and prior treatment with MPLA increases survival after otherwise lethal exposure to LPS in animal models (2,16,39). However, the effect of MPLA on the innate response to clinically relevant models of bacterial infection has not been determined.…”
mentioning
confidence: 99%